Chemical Biology of Sterols, Triterpenoids and Other Natural Products: A Themed Issue in Honor of Professor W. David Nes on the Occasion of His 65th Birthday - Guo, De-an (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Sterols and other isoprenoids are of great interest for their molecular structure and function in cell architecture and evolution, as well as for their importance in medicine and agriculture. Molecules' 2019 Festschrift Special Issue in honor of the 65th birthday of Prof. W. David Nes, an internationally recognized chemical biologist and recipient of the George Schroepher medal for sterol research, focuses on recent developments in the chemistry, biosynthesis, and function of these polycyclic natural products. This volume of Molecules contains 16 leading-edge review articles and original research contributions from an international cast of scientists. This volume is grouped into three sections: (i) isoprenoid metabolome and diversity, (ii) clinical evaluation of sterol and triterpene structures and biosynthesis, and (iii) methods and synthesis of steroids and other compounds. The volume will be a valuable reference tool for those who study medicinal chemistry, protein chemistry, and biochemistry of isoprenoid lipids.